Seismic Resistance of Non-Linearly Deformable Large-Span Spatial Structures of Unique Buildings - Saidmaksud R. Razzakov (Железобетонные конструкции)
Analytical, computer and experimental modeling methods are applied in the study of seismic resistance and changing dynamic parameters of long-term loaded non-linearly deformed large-span spatial shell structures. Physically and geometrically nonlinear deformation models and computational algorithms for solving dynamic problems are proposed for estimating the stress-strain state of smooth and ribbed spatial systems with variable stiffness caused by damage accumulation and orthotropic structure reinforced by ribs. The possibility of using the proposed method of taking into account variable dynamic stiffness in calculations for solving problems of dynamic strength and stability of spatial large-span shells of unique buildings of complex geometry is shown.